Wavelet transform in investigations of students educability dependently on degree of grafical skills automation of writing process - Bilous, N.; Kozina, O.; Zapolovskij, M.; Panchenko, V. (ITHEA, 2010)
Application of 2-level 2-D Haar Discrete Wavelet Transform of images with special words repeated by hand is offered. Metric of similarity for images with pattern words and images with students' written words like analog of proposed patterns is considered. A new approach to objective assessment of educability like dependence on level of graphic skills of process of writing is offered. Experiment is revealed the presence of statistic significant correlation between average score in special academic subjects group or in other words between special educability and level of graphic writing skills automation for high school students.
Keywords: educability; process of writing; 2D discrete wavelet transform; image similarity